THE INFLUENCE OF STUDENTS’ READING HABIT AND TEACHERS’ ROLE ON STUDENTS’ READING ACHIEVEMENT - Nesy Marantina (Universitas PGRI Palembang, 2013)
ABSTRACTThis study aimed at finding out whether or not (1) there is a significant influence of students’ reading habit on students’ reading achievement; (2) there is a significant influence of teachers’ role on students’ reading achievement; and(3)there is a significant influence of students’ reading habit and and teachers’ role on students’ reading achievement. The population of this study consisted of 174 students of SMPN 23 in the academic year of 2012/2013. The writer took all theeleventh grade students as the sample of the study. The sample was selected by using purposive sampling. The data were collected by using questionnaires and test. The data were analyzed by using correlation (spearman rho) and regression analyses. The result showed that there was a significant relationship between students’ reading habit and students’ reading achievement (r=.346); there was asignificant relationship between teachers’ role and English Reading achievement (r=.367); there was a significant relationship among students’ reading habit and teachers’ role on students’ reading achievement (r=.377). The influence orcontribution of students’ reading habit was 0.087 or 8.7% to the students’ reading achievement and the influence or contribution of teachers’ role was 0.120 or 12.0% to the students’ reading achievement. The variability of English Reading achievement could be explained 14.2% by students’ reading habit and teachers’ role in learning. The rest (85.8%) was determined by other factors.Key Word: Influence, Students’ Reading Habit, Teachers’ Role, and Reading Achievement